Indigenous Food Systems and Climate Change: Impacts of climatic shifts on the production and processing of native and traditional crops in the Bolivian Andes - Alder eKeleman Saxena; Ximena eCadima Fuentes; Rhimer eGonzales Herbas; Debbie L. Humphries (Frontiers Media S.A., 2016)
Inhabitants of the high-mountain Andes have already begun to experience changes in the timing, severity, and patterning of annual weather cycles. These changes have important implications for agriculture, for human health, and for the conservation of biodiversity in the region. This paper examines the implications of climate-driven changes for native and traditional crops in the municipality of Colomi, Cochabamba, Bolivia. Data was collected between 2012 and 2014 via mixed-methods, qualitative fieldwork, including participatory workshops with female farmers and food preparers, semi-structured interviews with local agronomists, and participant observation. Drawing from this data, the paper describes a) the observed impacts of changing weather patterns on agricultural production in the municipality of Colomi, Bolivia; and b) the role of local environmental resources and conditions, including clean running water, temperature, and humidity, in the household processing techniques used to conserve and sometimes detoxify native crop and animal species, including potato (Solanum sp.), oca (Oxalis tuberosa), tarwi (Lupinus mutabilis), papalisa (Ullucus tuberosus), and charkay (llama or sheep jerky). Analysis suggests that the effects of climatic changes on agriculture go beyond reductions in yield, also influencing how farmers make choices about the timing of planting, soil management, the use and spatial distribution of particular crop varieties. Further, household processing techniques to preserve and detoxify native foods rely on key environmental and climatic resources, which may be vulnerable to climatic shifts. While these findings are drawn from a single case-study, we suggest that Colomi agriculture characterizes larger patterns in what might be termed, indigenous food systems. Such systems are underrepresented in aggregate models of the impacts of climate change on world agriculture, and may be under different, more direct, and more immediate threat from climate change. As such, the health of the food production and processing environments in such systems merits immediate attention in research and practice.